The Prevalence and Incidence of Dementia: a Systematic Review and Meta-analysis. (April 2016) - Fiest, Kirsten M.; Jetté, Nathalie; Roberts, Jodie I.; Maxwell, Colleen J.; Smith, Eric E.; Black, Sandra E.; Blaikie, Laura; Cohen, Adrienne; Day, Lundy; Holroyd-Leduc, Jayna; Kirk, Andrew; Pearson, Dawn; et al.
Abstract: Introduction: Dementia is a common neurological condition affecting many older individuals that leads to a loss of independence, diminished quality of life, premature mortality, caregiver burden and high levels of healthcare utilization and cost. This is an updated systematic review and meta-analysis of the worldwide prevalence and incidence of dementia. Methods: The MEDLINE and EMBASE databases were searched for relevant studies published between 2000 (1985 for Canadian papers) and July of 2012. Papers selected for full-text review were included in the systematic review if they provided an original population-based estimate for the incidence and/or prevalence of dementia. The reference lists of included articles were also searched for additional studies. Two individuals independently performed abstract and full-text review, data extraction, and quality assessment of the papers. Random-effects models and/or meta-regression were used to generate pooled estimates by age, sex, setting (i.e., community, institution, both), diagnostic criteria utilized, location (i.e., continent) and year of data collection. Results: Of 16, 066 abstracts screened, 707 articles were selected for full-text review. A total of 160 studies met the inclusion criteria. Among individuals 60 and over residing in the community, the pooled point and annual period prevalence estimates of dementia were 48.62 (CI95% : 41.98-56.32) and 69.07 (CI95% : 52.36-91.11) per 1000 persons, respectively. The respective pooled incidence rate (same age and setting) was 17.18 (CI95% : 13.90-21.23) per 1000 person-years, while the annual incidence proportion was 52.85 (CI95% : 33.08-84.42) per 1, 000 persons. Increasing participant age was associated with a higher dementia prevalence and incidence. Annual period prevalence was higher in North America than in South America, Europe and Asia (in order of decreasing period prevalence) and higher in institutional compared to community and combined settings. Sex, diagnostic criteria (except for incidence proportion) and year of data collection were not associated with statistically significant different estimates of prevalence or incidence, though estimates were consistently higher for females than males. Conclusions: Dementia is a common neurological condition in older individuals. Significant gaps in knowledge about its epidemiology were identified, particularly with regard to the incidence of dementia in low- and middle-income countries. Accurate estimates of prevalence and incidence of dementia are needed to plan for the health and social services that will be required to deal with an aging population. RÉSUMÉ: Prévalence et incidence de la démence : revue systématique et méta-analyse . Contexte: La démence est une maladie neurologique fréquente touchant de nombreuses personnes âgées. Elle est la cause de la perte de l'indépendance, d'une qualité de vie altérée, d'une mortalité prématurée et constitue un fardeau important pour les soignants. Elle entraîne une utilisation et un coût élevé de soins de santé par ces patients. Nous avons effectué une revue systématique et une méta-analyse à jour de la prévalence et de l'incidence de la démence à travers le monde. Méthodologie: Nous avons identifié les études pertinentes publiées entre 2000 (1985 pour les publications canadiennes) et juillet 2012 dans les bases de données MEDLINE et EMBASE. Les articles choisis pour un examen du texte intégral ont été inclus dans l'examen systématique s'ils fournissaient une estimation originale à l'échelle populationnelle de l'incidence et/ou de la prévalence de la démence. Nous avons également recherché des études additionnelles dans la liste de références incluse dans ces articles. Deux évaluateurs ont revu indépendamment les résumés et le texte intégral des publications ainsi que l'extraction des données et ils en ont évalué la qualité. Nous avons utilisé des modèles à effets aléatoires et/ou de méta-régression pour générer des estimations regroupées par âge, sexe, milieu (communauté, institution ou les deux), critères diagnostiques utilisés, lieu (continent), et année de collecte des données. Résultats: Parmi les 16 066 résumés revus, 707 articles ont été choisis pour une revue du texte intégral. En tout, 160 articles rencontraient les critères d'inclusion. Chez les individus de 60 ans et plus demeurant dans la communauté, les estimés regroupés de prévalence ponctuelle et annuelle de démence étaient de 48, 62 (IC à 95%: 41, 98 à 56, 32) et 69, 07 (IC à 95%: 52, 36 à 91, 11) par 1 000 personnes respectivement. Le taux d'incidence regroupée (même âge et contexte) était de 17, 18 (IC à 95%: 13, 90 à 21, 23) par 1 000 personnes-années alors que la proportion d'incidence annuelle était de 52, 85 (IC à 95%: 33, 08 à 84, 42) par 1 000. Un âge croissant des participants était associé à une prévalence et à une incidence plus élevées de démence. La prévalence annuelle pour une période donnée était plus élevée en Amérique du Nord qu'en Amérique du Sud, en Europe ou en Asie (en ordre décroissant de prévalence par période) et plus élevée dans un contexte institutionnel par rapport à la communauté et aux deux contextes combinés. Le sexe, les critères diagnostiques (sauf pour la proportion d'incidence) et l'année de la collecte des données n'étaient pas associés à des estimations de prévalence ou d'incidence significativement différentes au point de vue statistique, bien que les estimations étaient constamment plus élevées chez les femmes que chez les hommes. Conclusions: La démence est une maladie neurologique fréquente chez les individus plus âgés. Nous avons identifié d'importantes lacunes dans les connaissances sur l'épidémiologie, particulièrement en ce qui concerne l'incidence de la démence dans les pays à revenu faible et intermédiaire. Des estimations exactes de la prévalence et de l'incidence de la démence sont nécessaires pour la planification des services de santé et des services sociaux qui seront requis par une population vieillissante.